If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (A)(b) = (b)(a) Multiply A * b bA = (b)(a) Multiply b * a bA = ab Solving bA = ab Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1ab' to each side of the equation. -1ab + bA = ab + -1ab Combine like terms: ab + -1ab = 0 -1ab + bA = 0 Factor out the Greatest Common Factor (GCF), 'b'. b(-1a + A) = 0Subproblem 1
Set the factor 'b' equal to zero and attempt to solve: Simplifying b = 0 Solving b = 0 Move all terms containing b to the left, all other terms to the right. Simplifying b = 0Subproblem 2
Set the factor '(-1a + A)' equal to zero and attempt to solve: Simplifying -1a + A = 0 Reorder the terms: A + -1a = 0 Solving A + -1a = 0 Move all terms containing b to the left, all other terms to the right. Add '-1A' to each side of the equation. A + -1A + -1a = 0 + -1A Combine like terms: A + -1A = 0 0 + -1a = 0 + -1A -1a = 0 + -1A Remove the zero: -1a = -1A Add 'a' to each side of the equation. -1a + a = -1A + a Combine like terms: -1a + a = 0 0 = -1A + a Simplifying 0 = -1A + a The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
b = {0}
| -9+2z=9z-1+3 | | -7-5(5+7b)=248 | | 8=7(x+5)-8x | | -7(5+5x)=105 | | 5/6(x+6) | | x^3+7x^2+2x-42=0 | | 6030+0.04x/67000+x | | 3a-3/2=-21/4 | | 4a+12r=4.6 | | -8(n-7)=112 | | 4-(-8x+5)=-32x-26 | | 8d-32+3d-32=5 | | 4x^2-x-11=0 | | x+2/x+1=x-4/x-3 | | 11x+14=95-16x | | 4x+2=3(4x+1) | | 4(2x-5)=52 | | 8(6+8v)-2v=172 | | 21/b=147/105 | | -3t=8t | | (2x-5)=52 | | 4.3x+8x=12.3 | | 8a+6r=4.7 | | 4/(-5)=2x-1/2 | | q=250-5p | | 2p+6=4p+10 | | 15z=-9z | | 7(-3n-4)+2n=-123 | | y=4x^2+27x-7 | | -29=5w+6-12w | | 10t-3t-1=13 | | 81=0.5h(6+3) |